Working at Webboyz: An Analysis of Control over the Software Development Labour Process. - Barrett, Rowena (Sociology, 2004)
This article explores how management constructs strategies to control the labour-process of software development, through a case study of a small Australian software development company, Webboyz Pty Ltd. This firm employs mainly young, male software developers to develop internet tools and e-commerce software and solutions for different segments of the local and international software market. Distinguishing between primary and secondary software products, and their associated production processes, provides a way of analysing the organization and control of software development work. The case study of Webboyz reveals how management strategies to control the labour process of software development are influenced by the type of product being developed and the timing in the product's development lifecycle as well as the type of workers developing the software product. Reprinted by permission of the publisher.